Physical, structural and sensory properties of wafer batter and wafer sheets influenced by various sources of grains. (September 2021) - Nasabi, Mahshad; Naderi, Behnaz; Akbari, Mehdi; Aktar, Tugba; Kieliszek, Marek; Amini, Mehdi
Abstract: This study aimed to investigate the effect of alternative, non-wheat flours on the rheological properties of wafer batter as well as textural and sensory attributes of wafer sheet. The results indicated that the highest weight and moisture content were observed in wafers containing barley and oat flours. The addition of non-wheat flours other than maize (corn) flour led to a higher viscosity compared with the control batter. Wafer containing rye flour had the lowest hardness and the highest porosity (88.2%) among all samples. Non-wheat flours improve the nutritional value of the wafer; however, the addition of these flours to the wafer can change the rheological properties of the wafer batter and final product quality. Among the tested alternative non-wheat flours, maize flour showed the greatest similarity to wheat flour in terms of viscosity, which is the most important property of the wafer batter. According to the results, it is feasible to use non-wheat flours in a wafer with improved nutritional properties. Highlights: Replacement non-wheat flours, altered the final product quality. Wafer containing rye flour had the lowest hardness and the highest porosity. Corn flour was the most similar to wheat flour in terms of viscosity.